PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ASN BPKAD PROVINSI SUMATERA SELATAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Sakarina, Sari; Noviantoro, Djatmiko; kesuma, muhammad jaka (LPPM Universitas Multi Data Palembang, 2024)
ABSTRACT Muhammad Jaka Kesuma, The Effect of Leadership and Work Environment on the Performance of ASN Employees of BPKAD South Sumatra Province with Work Motivation as a Mediating Variable, Supervisors Dr. Djatmiko Noviantoro, SE., M.Si and Dr. Sari Sakarina, SE., MM. This study aims to determine and prove and analyze the Direct Effect, namely the Effect of leadership on work motivation, the Effect of work environment on work motivation, the Effect of leadership on performance, the Effect of work environment on performance and the Effect of work motivation on performance with the Sample in this study are ASN Employees of BPKAD South Sumatra Province totaling 84 people. Data analysis of the study uses descriptive and inferential statistical methods. The analysis model uses Structural Equation Model (SEM) with the composition of Sub-structure: Leadership and Work Environment as exogenous variables, Employee Performance endogenous variable, and Motivation as Intervening variable. From the results of testing the Hypothesis, it was found as follows: 1) There is an Effect of Leadership on Work Motivation of ASN Employees of BPKAD South Sumatra Province, 2) There is an Effect of Work Environment on Work Motivation of ASN Employees of BPKAD South Sumatra Province, 3) There is an Effect of Leadership on Employee Performance of ASN BPKAD South Sumatra Province, 4) There is an Effect of Work Environment on Employee Performance of ASN BPKAD South Sumatra Province, 5) There is an Effect of Work Motivation on Employee Performance of ASN BPKAD South Sumatra Province. Keywords: Leadership, Work Environment, Motivation and Performance